Loss of CITED1, an MITF regulator, drives a phenotype switch in vitro and can predict clinical outcome in primary melanoma tumours - Howlin,Jill; Cirenajwis,Helena; Lettiero,Barbara.; Staaf,Johan; Lauss,Martin; Saal,Lao; Borg,Åke; Gruvberger-Saal,Sofia K; Jönsson,Göran B (PeerJ PrePrints, 2014)
CITED1 is a non-DNA binding transcriptional co-regulator whose expression can distinguish the ‘proliferative’ from ‘invasive’ signature in the phenotype-switching model of melanoma. We have found that CITED1 expression is repressed by TGFβ in addition to other ‘proliferative’ signature genes while the ‘invasive’ signature genes are upregulated. In agreement, CITED1 positively correlates with MITF expression and can discriminate the MITF-high/pigmentation tumor molecular subtype in a large cohort (120) of melanoma cell lines. Interestingly, CITED1 overexpression significantly suppressed MITF promoter activation, mRNA and protein expression levels while MITF was transiently upregulated following siRNA mediated CITED1 silencing. Conversely, MITF siRNA silencing resulted in CITED1 downregulation indicating a reciprocal relationship. Whole genome expression analysis identified a phenotype shift induced by CITED1 silencing and driven mainly by expression of MITF and a cohort of MITF target genes that were significantly altered. Concomitantly, we found changes in the cell-cycle profile that manifest as transient G1 accumulation, increased expression of CDKN1A and a reduction in cell viability. Additionally, we could predict survival outcome by classifying primary melanoma tumors using our in vitro derived ‘CITED1-silenced’ gene expression signature. We hypothesize that CITED1 acts a regulator of MITF, functioning to maintain MITF levels in a range compatible with tumourigenesis.
Keywords: CITED1; MITF; MELANOMA; PHENOTYPE-SWITCHING MODEL; MOLECULAR SUBTYPE